Obstetric and perinatal characteristics in pregnant women with SARS-CoV-2. Dos de Mayo National Hospital - Aparicio-Ponce, Jorge Renato (2022)
Introduction: The COVID-19 pandemic starts in Peru in March 2020. It appears that progression to severe forms of the disease in pregnant women is infrequent. The most frequent complications are premature rupture of membranes, premature delivery and fetal distress. Vertical transmission has not been demonstrated. National studies are mostly only from the first stage of the pandemic. Objective: determine the epidemiological, obstetric and perinatal characteristics in pregnant women with SARS-CoV-2. Material and methods: A descriptive study was conducted at the Hospital Nacional Dos de Mayo. A total of 579 SARS-CoV-2 positive pregnant women and 533 newborns were admitted. Medical records were reviewed. Descriptive statistics were performed. The study is registered in PRISA with code EI00002469. Results: SARS-CoV-2 was detected by serological antibodies in 91.0% and in 8.0% by antigenic test. Of the cases, 94.5% (547/579) remained asymptomatic. Nineteen cases (3.3%) were complicated by COVID-19 pneumonia. There were no obstetric complications in 65.5%; the most common were premature rupture of membranes (9,7%), preeclampsia (8,2%) and urinary tract infection (5,0%). Neonatal characteristics such as gestational age, birth weight and Apgar were mostly within normal limits. Conclusion: that pregnant women with SARS-CoV-2 are mostly asymptomatic, have a low frequency of complications and the newborns do not present major complications.